Atmospheric Cold Front-Generated Waves in the Coastal Louisiana - Yuhan Cao; Chunyan Li; Changming Dong (Journal of Marine Science and Engineering, 2020)
Atmospheric cold front-generated waves play an important role in the air–sea interaction and coastal water and sediment transports. In-situ observations from two offshore stations are used to investigate variations of directional waves in the coastal Louisiana. Hourly time series of significant wave height and peak wave period are examined for data from 2004, except for the summer time between May and August, when cold fronts are infrequent and weak. The intra-seasonal scale variations in the wavefield are significantly affected by the atmospheric cold frontal events. The wave fields and directional wave spectra induced by four selected cold front passages over the coastal Louisiana are discussed. It is found that significant wave height generated by cold fronts coming from the west change more quickly than that by other passing cold fronts. The peak wave direction rotates clockwise during the cold front events. The variability of the directional wave spectrum shows that the largest spectral density is distributed at low frequency in the postfrontal phase associated with migrating cyclones (MC storms) and arctic surges (AS storms).